Thyroid carcinoma in woman. gynecologist view - Т. Ф. Татарчук; Л. В. Калугіна; А. О. Данилова (Репродуктивная эндокринология, 2019)
Over the past decade the incidence of thyroid cancer in Ukraine has increased 1.5 times, and the average age of diagnosis among women is 36 years. Thyroid cancer is the most common endocrine cancer, occurs in 5–10% of patients with thyroid nodules. Papillary carcinoma is 80% of all thyroid malignant neoplasms and is three times more common in women than in men. The peak incidence in women is observed in 40–49 years, while in men the peak is 60–69 years.